2019
DOI: 10.31921/doxacom.n29a1
|View full text |Cite
|
Sign up to set email alerts
|

What does the digital press talk about when it talks about nutrition? An analysis of elpais.com and lavanguardia.com during 2017

Abstract: News on nutrition has become a regular feature on the media agenda. This paper analyses characteristics of texts on this topic published during 2017 in the digital editions of El País and La Vanguardia, the two newspapers with the widest circulation in Spain. The study looked in greater depth at aspects such as the main topics being addressed, authorship, genres and headlines of the texts, framing, sources and the number of comments from readers. The two chosen newspapers reveal considerable differences in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The interest in information on nutrition among the Western population is a fact. A study conducted by ComScore (2018) on Internet users in Germany, France, the United Kingdom, Spain and Italy found that at least 130 million people visited a diet website in 2018 [97]. It has been seen in the US that there is an increasing demand for health information [98] and that the Internet is where 59% of Americans are going to look for it [99].…”
Section: Discussionmentioning
confidence: 99%
“…The interest in information on nutrition among the Western population is a fact. A study conducted by ComScore (2018) on Internet users in Germany, France, the United Kingdom, Spain and Italy found that at least 130 million people visited a diet website in 2018 [97]. It has been seen in the US that there is an increasing demand for health information [98] and that the Internet is where 59% of Americans are going to look for it [99].…”
Section: Discussionmentioning
confidence: 99%